1982
DOI: 10.1128/aem.44.6.1249-1252.1982
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Production of Ursodeoxycholic Acid from Lithocholic Acid by Fusarium equiseti M41

Abstract: A fungus identified as Fusarium equiseti was isolated from soil and found to carry out 7,3-hydroxylation of lithocholic acid to ursodeoxycholic acid (35% yield; 350 mg/liter) in 112 h.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
1

Year Published

1985
1985
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 12 publications
0
13
1
Order By: Relevance
“…Therefore, for the design of a biotransformation study involving hydrophobic substrates, it is critical to consider the adsorption capacity of each microorganism. From our experience in the screening of bile acid transformers (16,22), a high binding capacity for bile acids is a prerequisite for the high transformation of the substrate.…”
Section: Downloaded Frommentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, for the design of a biotransformation study involving hydrophobic substrates, it is critical to consider the adsorption capacity of each microorganism. From our experience in the screening of bile acid transformers (16,22), a high binding capacity for bile acids is a prerequisite for the high transformation of the substrate.…”
Section: Downloaded Frommentioning
confidence: 99%
“…In studying the biotransformation of steroidal compounds (13,(15)(16)(17)22), we found Fusarium equiseti M41 to transform lithocholic acid (LCA) into ursodeoxycholic acid (UDCA), a gallstone solubilizer that is effective in humans (20,24). We found that this fungus required a concentration of LCA higher than is necessary for it to be soluble in water for its efficient conversion to UDCA, and that insoluble LCA particles attached to the mycelia of F. equiseti M41.…”
mentioning
confidence: 99%
“…Assay. Bile acid content was determined gas chromatographically after derivatization with hexafluoroisopropanol and trifluoroacetic anhydride (17) as described before (25), using cholic acid as an internal standard. The relative retension times of UDCA, LCA, and a by-product against cholic acid were 0.67, 0.29, and 0.89, respectively.…”
Section: 07mentioning
confidence: 99%
“…In a previous paper (25) we reported the formation of UDCA, using one-step transformation from lithocholic acid (LCA; 3ot-hydroxy-5,B-cholanic acid), by Fusarium equiseti M41. In this paper we report the optimization of biotransformation of LCA into UDCA.…”
mentioning
confidence: 99%
“…Research with steroid biotransformations by intestinal bacteria has emphasized the three major classes of steroids which pass through the GI tract; these are the bile acids (43,78,92,94,103), cholesterol (18,39,143,147), and steroid hormones (14,16,154). Although this review will almost exclusively deal with bacteria, it should be noted that protozoa and fungi can also play an important role in steroid biotransformations (21,60,121).…”
Section: Bacterial Transformations Of Steroids In the Gastrointestinamentioning
confidence: 99%